Assessment of Organic Carbon Stocks at Landscape Levels Using the InVEST Software - Drygval, Polina; Drygval, Anna; Tabunshchik, Vladimir (Salehan Institute of Higher Education, 2025)
This study aims to calculate and assess organic carbon levels at various landscape levels of the Crimean Peninsula using the Carbon Storage and Sequestration model of the InVEST software. It outlines the stages of working with this model and highlights limitations such as the quality of input data, temporal coverage, and spatial resolution, which can significantly influence the results. Assessment of organic carbon stocks in soils, aboveground and belowground biomass, and vegetation types revealed that the highest carbon concentration was in the low-altitude landscape level of the southern macroslope. From 2017 to 2023, an annual decrease in organic carbon stocks of 0.062 t/ha was recorded, which is likely linked to climate change and shifts in land use. This research provides the first calculations of organic carbon content within the landscape levels of the Crimean Peninsula. As carbon is a significant greenhouse gas, its accumulation or emissions directly affect climate change. Evaluating organic carbon stocks in ecosystems enhances our understanding of their role in mitigating climate change and informing carbon dioxide (CO2) reduction strategies. These findings highlight the need to consider vegetation types and their changes when calculating organic carbon in landscapes and supporting regional environmental policy development. Doi: 10.28991/CEJ-2025-011-03-018 Full Text: PDF